Partnership Firms, Reputation, and Human Capital - Morrison, Alan D; Wilhelm, William J (American Economic Review, 2004)
In human capital intensive industries where it is difficult to contract upon the training effort of skilled agents a socially suboptimal level of training may occur. We show how partnership organisations can overcome this problem by tying human and financial capital. Partnerships are opaque so that the willingness of clients to pay depends upon reputation. Partnerships are illiquid and partners must stay with the firm until clients discover their type and update the firm's reputation. This renders unskilled agents, who will aversely affect reputation, unwilling to accept partnerships. Skilled agents therefore train the next generation so as to ensure that there is an adequate market for their own shares. We comment upon the salient differences between partnerships and joint stock firms.